2007
DOI: 10.3324/haematol.11318
|View full text |Cite
|
Sign up to set email alerts
|

Low vitamin B6 levels and the risk of recurrent venous thromboembolism

Abstract: Low plasma vitamin B6, measured as pyridoxal-5'-phosphate (PLP), is associated with an increased risk of first venous thromboembolism (VTE). In a prospective cohort of 757 patients with first VTE we investigated the association of PLP levels with risk of recurrent VTE. After 4 years, the likelihood of VTE recurrence was 22.5% (95% CI 13.6-31.5%) among patients with PLP ≤23.3 nmol/L and 14.4% (11.5-17.4%) among those with PLP >23.3 nmol/L (p=0.01). Patients with PLP ≤23.3 nmol/L had 1.8-fold higher recurrence r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 21 publications
2
16
0
3
Order By: Relevance
“…However, in patients with a combination of liver disease and poor nutritional status, such as for alcoholics (1.5 g alcohol/kg/d, >5 years) (43), the risk for pyridoxine deficiency is increased (44). Clinical manifestations of pyridoxine phosphate deficiency are typically unrelated to hyperhomocysteinemia, but observational studies have linked low pyridoxine phosphate levels with an increased risk for first-time and recurrent venous thromboembolism (45). Data from an uncontrolled intervention trial suggested that high dose pyridoxine supplementation decreases the incidence of thromboembolism in patients with homocystinuria (RR=0.09, 95% CI 0.02-0.38) (46); however, the benefit of routine surveillance or treatment of low pyridoxine phosphate levels in the general population remains unknown.…”
Section: Biochemistrymentioning
confidence: 99%
“…However, in patients with a combination of liver disease and poor nutritional status, such as for alcoholics (1.5 g alcohol/kg/d, >5 years) (43), the risk for pyridoxine deficiency is increased (44). Clinical manifestations of pyridoxine phosphate deficiency are typically unrelated to hyperhomocysteinemia, but observational studies have linked low pyridoxine phosphate levels with an increased risk for first-time and recurrent venous thromboembolism (45). Data from an uncontrolled intervention trial suggested that high dose pyridoxine supplementation decreases the incidence of thromboembolism in patients with homocystinuria (RR=0.09, 95% CI 0.02-0.38) (46); however, the benefit of routine surveillance or treatment of low pyridoxine phosphate levels in the general population remains unknown.…”
Section: Biochemistrymentioning
confidence: 99%
“…An increased risk of recurrent VTE has been reported in subjects with high levels of thrombin-activable fibrinolysis inhibitor (TAFI) [89], low vitamin B6 levels [90], low levels of free tissue factor pathway inhibitor (TFPI) [91], and elevated albuminuria [92] while high levels of apolipoprotein A1 and HDL have not been reported as being associated with lower risk of recurrence [93]. …”
Section: Risk Factors For Recurrencementioning
confidence: 99%
“…The consequences of marginal deficiency are unclear, but chronically low vitamin B6 status is associated with increased risk of cardiovascular disease [12][17], deep-vein thrombosis [18][20], stroke [21] and certain cancers [22], [23]. The mechanisms responsible for these disease connections are unknown but do not appear to be associated with hyperhomocysteinemia [5].…”
Section: Introductionmentioning
confidence: 99%